Immersive 3D Digital Twin for Collaborative Hydrogen Pipeline Simulation and Visualization: A Project Description - Sarvesh, Muskan; Kang, Ryan; Marzban, Mehdi; Cho, Isaac; Park, Simon; Hugo, Ron; Kim, Kangsoo (2024 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2024)
This paper introduces our plan to develop a 3D pipeline engineering tool, building upon our in-house web-based Pipeline Reliability and Integrity Management Engineering tool (PRIME), to address the limitations of traditional 2D data visualization in pipeline management. Leveraging immersive technologies, such as Virtual Reality (VR), the tool enhances simulation capabilities, introducing features like multi-user communication, digital twin integration, and virtual site visits. The study proposed in the paper aims to evaluate the tool's potential by comparing it to the existing web application, focusing on immersive training, collaboration tools, 3D data visualization, and environmental conditions in the pipeline maintenance workflows. This research aspires to contribute to the field of immersive technologies in pipeline operations, offering a comprehensive understanding of their impact on efficiency and impactful decision-making.